Phosphorylation of multifunctional galectins by protein kinases CK1, CK2, and PKA - Kübler, Dieter; Seidler, Jörg; André, Sabine; Kumar, Sonu; Schwartz-Albiez, Reinhard; Lehmann, Wolf-Dieter; Gabius, Hans-Joachim (Analytical biochemistry, 2014)
Phosphorylation is known to have a strong impact on protein functions. We analyzed members of the lectin family of multifunctional galectins as targets of the protein kinases CK1, CK2, and PKA. Galectins are potent growth regulators able to bind both glycan and peptide motifs at intra- and extracellular sites. Performing in vitro kinase assays, galectin phosphorylation was detected by phosphoprotein staining and autoradiography. The insertion of phosphoryl groups varied to a large extent depending on the type of kinase applied and the respective galectin substrate. Sites of phosphorylation observed in the recombinant galectins were determined by a strategic combination of phosphopeptide enrichment and nano-ultra-performance liquid chromatography tandem mass spectrometry (nanoUPLC-MS/MS). By in silico modeling, phosphorylation sites were visualized three-dimensionally. Our results reveal galectin-type-specific Ser-/Thr-dependent phosphorylation beyond the known example of galectin-3. These data are the basis for functional studies and also illustrate the analytical sensitivity of the applied methods for further work on human lectins.
Available online 10 December 2013
Gesehen am 22.06.2021